2017
DOI: 10.1016/j.oftal.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Seguridad clínica y reclamaciones por responsabilidad profesional en Oftalmología

Abstract: Professionals must be aware of the fundamental aspects of medical professional liability, as well as specific aspects, such as defensive medicine and clinical safety. The understanding of these medical-legal aspects in the routine clinical practice can help to pave the way towards a satisfactory and safe professional career, and help in increasing patient safety. The aim of this review is to contribute to this training, for the benefit of professionals and patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Our study showed that the ground for complaints are both reasons related to technical aspects of the medical activity and reasons related to the relationship between patients and medical staff, these results are consistent with literature data [ 14 ]. The analysis of these reasons is important so as to improve the medical practice by identifying various prevention methods that target both the medical practice and the doctor–patient relationship, to improve medical services provided to patients, and to protect the medical staff from complaints [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our study showed that the ground for complaints are both reasons related to technical aspects of the medical activity and reasons related to the relationship between patients and medical staff, these results are consistent with literature data [ 14 ]. The analysis of these reasons is important so as to improve the medical practice by identifying various prevention methods that target both the medical practice and the doctor–patient relationship, to improve medical services provided to patients, and to protect the medical staff from complaints [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The medical practice has been regulated throughout its entire historical evolution by specific legal and ethical norms, which are aimed at carrying out the medical act in optimal conditions, protecting the patients, and sanctioning the doctors who violate the norms of good practice [ 1 ]. Medicine and science, in general, enjoy quasi-constant advancements, which bring multiple benefits through their wide applicability [ 2 ]. Nonetheless, by increasing public expectations, emphasizing the publicity of patient rights [ 1 , 3 ] and the marketing of medicine [ 3 ], the progress in technology places a greater burden on the shoulders of the doctors, which often leads patients to have unrealistic expectations and causes them to sanction any mistake or any result that does not coincide with their expectations [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations